2010
DOI: 10.1017/s1751731109990899
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pasture availability for twin- and triplet-bearing ewes in mid and late pregnancy on ewe and lamb behaviour 12 to 24 h after birth

Abstract: This experiment was conducted to evaluate the effect of offering ewes two different feeding levels, during mid and late pregnancy, on ewe and lamb behaviour 12 to 24 h after birth. Romney ewes, bearing twin (n = 80) or triplet foetuses (n = 56), were allocated to a pasture sward height of 2 or 4 cm between 70 and 107 days of pregnancy. In late pregnancy (day 107 to 147), half of the ewes were reallocated the alternate sward height, which produced four treatments: 2-2, 2-4, 4-2 and 4-4. Ewes were weighed on day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Rech et al (2008) reported that ewes with higher MBS protected their lambs more soon after birth and weaned heavier lambs. Several factors may influence maternal behavior (Hernandez, Matthews, Oliver, Bloomfield, & Harding, 2009;Corner et al, 2010), such as previous experience, breed, ewe body condition score, nutritional state, production system and other factors. Since young females may show little or no ability (Mariz et al, 2007;Dwyer, 2008;Dwyer, 2014), they reduce lamb viability without human interference.…”
Section: Introductionmentioning
confidence: 99%
“…Rech et al (2008) reported that ewes with higher MBS protected their lambs more soon after birth and weaned heavier lambs. Several factors may influence maternal behavior (Hernandez, Matthews, Oliver, Bloomfield, & Harding, 2009;Corner et al, 2010), such as previous experience, breed, ewe body condition score, nutritional state, production system and other factors. Since young females may show little or no ability (Mariz et al, 2007;Dwyer, 2008;Dwyer, 2014), they reduce lamb viability without human interference.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from the present study are in agreement with the above statement, where the lamb that was quicker to stand after birth was also quicker at making a successful attempt at suckling. In addition, the quicker attempt at suckling made by lambs born to undernourished ewes in this study may be partially explained by work performed by Corner et al (2010), where lambs born to nutritionally restricted ewes were perceived as being more aggressive in terms of maternal recognition and consequently were quicker to move toward the ewe after birth. In contrast to previous studies where a nutritional restriction during gestation negatively affected maternal behavior at parturition (Dwyer et al, 2003), a,b Within a row, means without a common superscript differ significantly (P < 0.05).…”
Section: Discussionmentioning
confidence: 76%
“…It would be expected, however, the relationship between the frequency of high-bleats and lamb survival would be similar between twin and triplet lambs. Corner et al [30] reported that a similar proportion of twin and triplet lambs were observed to bleat and at a similar frequency, although in that study low and high pitch bleats were not recorded separately. It is possible that the larger proportion of triplet lambs that died compared with twins may have altered the relationship between high bleat frequency and survival.…”
Section: Maternal-recognition Testmentioning
confidence: 83%